The Role of Artificial Intelligence in Fashion Design - Albishri, Amal Abdullah; Almisbahi, Ruba Majed (Advances in Social Sciences Research Journal, 2024)
This research investigates the role of artificial intelligence (AI) in fashion design, focusing on its potential to foster innovative and aesthetically striking designs. The study explores the level of interest among emerging fashion designers, including students from design and arts colleges, as well as individuals keen on distinctive and avant-garde fashion. The research aims to achieve its objectives using descriptive, analytical, and quasi-experimental methodologies. Findings reveal that while there is significant interest among fashion design students and professionals in AI-based design, challenges arise from the limited availability of learning resources, hindering their ability to fully grasp and apply this technology. The study concludes that there is an urgent need to integrate AI into fashion design education, as it can significantly benefit the industry and its practitioners. Recommendations include expanding specialised research connecting AI with fashion design, enhancing university curricula with crucial AI concepts, and focusing on technological advancements and AI applications in fashion design and forecasting.